Improved oxidation resistance of γ-TiAl intermetallics by sputtered Ni+CrAlYHfSiN composite coating. (15th July 2021) - Yang, Yingfei; Xiao, Qin; Ren, Pan; Li, Wei; Zhu, Shenglong; Wang, Fuhui
Highlights: Multiple longitudinal cracks appear in the sputtered NiCrAlYHfSi coating, but the Ni+CrAlYHfSiN coating is crack free. Multiple cracks accelerate the oxidation rate of the NiCrAlYHfSi coating. Due to the low TEC, the Ni+CrAlYHfSiN composite coating exhibits good resistance to cracking during oxidation. Owing to the "fix effect" of nitrides, the Ni+CrAlYHfSiN coating effectively inhibits Ti diffusing to the Al2 O3 scale. Abstract: NiCrAlYHfSi coating and Ni+CrAlYHfSiN coating were deposited on γ-TiAl alloy by magnetron sputtering. This work mainly focuses on the influence of cracks on the oxidation resistance of coatings, and the suppression cracking effect by doping nitrides. It was found that longitudinal cracks in the NiCrAlYHfSi coating increase with oxidation time prolonged. Cracks in NiCrAlYHfSi coating provide quick-diffusion channels for Ti and O ions. The Ni+CrAlYHfSiN coating is intact crack free during the whole oxidation process. Owing to the "fix effect" of nitrides, the Ni+CrAlYHfSiN composite coating effectively inhibits Ti diffusing to the surface to destroy the integrity of Al2 O3 scale.